Analisis Konsumen Produk Pangan pada Layanan Pesan Antar GrabFood di Wilayah Bandung Raya - Ananda, Vanya Dina; Wiyono, Sulistyodewi Nur; Budiman, Muhammad Arief; Utami, Hesty Nurul (Universitas Galuh, 2026)
The development of app-based food delivery services in Indonesia has shown significant growth in recent years. GrabFood has become one of the most widely used platforms, including in the Bandung Raya region, which is characterized by its urban demographics and high level of technology adoption. However, research specifically examining the consumer characteristics of food product users on the GrabFood platform within this region remains limited. This study aims to describe the characteristics of food product consumers using GrabFood services in Bandung Raya based on demographic, geographic, educational, income, and consumption pattern aspects. The research employed a descriptive quantitative approach using a survey method. A total of 250 Muslim respondents were selected through non-probability sampling techniques. Data were collected online through a Google Form questionnaire and analyzed using descriptive statistical techniques in the form of frequencies and percentages. The results indicate that GrabFood users are predominantly female, reside in urban areas, and possess relatively high educational backgrounds. In addition, most respondents fall within the middle-income category and demonstrate efficient consumption behavior in their daily food expenditures. These findings provide a comprehensive overview of the GrabFood consumer profile and offer valuable insights for businesses and digital platforms in formulating more targeted marketing strategies.